Towards perfect practice in South African court interpreting: A quality assurance and quality management model - Moeketsi, Rosemary M.H.; Mollema, Nina (International Journal of Speech, Language and the Law, 2006)
The Constitution of South Africa, Act 108 of 1996 at s35(3)(k) stipulates that ‘every accused person has a right to a fair trial, which includes the right to be tried in a language that the accused person understands or, if that is not practicable, to have the proceedings interpreted in that language’. The court interpreter is thus committed to making communication possible between litigants and court personnel within a multilingual and multicultural courtroom. Past and present records disclose many examples of incompetent interpreting and bad practices. The introduction of the concept of Perfect Interpreting Practice (PIP) aims at addressing the predicament of the South African court interpreter by transforming the service and inculcating a culture of commitment to quality, accountability and continuous improvement, where the focus is on the customer’s requirements. This paper considers the multifaceted complexities, as well as the challenges, which surround this type of courtroom communication, the characteristics of a quality interpreting service, as well as possible practical solutions to the problems such as reactive, flexibility-based and developmental training for interpreters.